Pengembangan instrumen skala general self-efficacy pada siswa sekolah menengah pertama - Athaya Yola Sevinka; Nyoman Dantes; Dewi Arum Widhayanti Metra Putri (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This research was conducted with the aim of producing a product in the form of a Self-efficacy Instrument for Grade VIII students of junior high schools in Kediri Regency. This study uses research with R&D research methods. The sampling technique uses a proportional stratified random sampling technique with a minimum sample of 175 students in 4 schools in the Kediri Regency, namely SMPN 1 Papar, SMPN 2 Papar, SMP Islam Kepung, SMPN 1 Gampengrejo. Then for the results of the CVR, a ΣCVR of 47.6 was obtained. And a CVI value of 0.95 which is categorized as